Comprehensive Assessment of Water Treatment Performance: A Case Study of Bhadgaun Water Supply Project - Chuwai, Bijaya; Pokhrel, Rajib (Journal of UTEC Engineering Management, 2025)
Ensuring an adequate supply of potable water in rapidly urbanizing regions poses increasing challenges due to limited water resources, aging infrastructure, and climate variability. This study evaluates the treatment efficiency of the Bhadgaun Water Supply Project by analyzing key physical (Turbidity, Electrical Conductivity (EC), pH, Total Dissolved Solid (TDS)) and microbiological (E. coli, Total Coliform) parameters across major treatment stages—sedimentation, roughing filtration, slow sand filtration, and chlorination—during both monsoon and dry seasons. Results showed significant seasonal variation, with monsoon water exhibiting turbidity up to 4.63 NTU, EC of 361 µS/cm, and E. coli counts as high as 96 CFU/100ml. The Slow Sand Filter achieved up to 84% turbidity and 71% E. coli reduction. Post-chlorination, microbial contamination was fully removed, ensuring compliance with National Drinking Water Quality Standard (NDWQS) 2022. TDS levels dropped from 261 mg/L to 103 mg/L during monsoon and from 112 mg/L to 76 mg/L during the dry season. Slight reductions in overall efficiency were observed in the dry season due to lower contaminant loads, affecting filter performance. It shows the effectiveness of the existing system and the need for regular monitoring and timely maintenance to ensure consistent delivery of safe drinking water.